Partition Dimension of Dutch Windmill Graph: Dimensi Partisi Graf Kincir Angin Belanda untuk siklus orde besar - Hasmawati, Hasmawati; Nurwahyu, Budi; Daming, Ahmad Syukur; Amir, Amir Kamal (Jurnal Matematika, Statistika dan Komputasi, 2021)
Let be a connected graph G and -partition of end . The coordinat to is definition . If every twovertex is distinct applies, then is a called partition of . The minimum k for which k-resolving partition of is the partition dimension and denoted with . In this paper, we investigates the partition dimensionfor a large Dutch windmill graph for and . We show that if for some, forany.